EVALUASI PELAKSANAAN PIS-PK DI PUSKESMAS KABUPATEN LABUAN BATU, PROVINSI SUMATERA UTARA DAN KOTA SEMARANG, PROVINSI JAWA TENGAH - Novianti Novianti; Ning Sulistiyowati; Oster Suriani Simarmata; Rachmalina S Prasodjo; Athena Anwar; Eva Laelasari; Joko Irianto (JURNAL EKOLOGI KESEHATAN, 2020)
ABSTRACT The Healthy Indonesia Program with Family Approach (PIS-PK) is an effort to strengthen basic health that began in 2015. To get more comprehensive data and information on the implementation of PIS-PK, in 2017 the Center for Public Health Efforts to carry out a PIS-PK evaluation study in several districts/cities in Indonesia. This study uses a quantitative and qualitative approach, in one puskesmas in Labuan Bajo Regency, North Sumatra Province and Semarang City, Central Java Province. Data collection was carried out by means of in-depth interviews about the implementation of PIS-PK including input indicators (personnel, funds, tools and methods), processes (planning, implementation, supervision), and output. The results of the study show that the implementation of input indicators, such as the limited number of Puskesmas human resources in data collection and data entry, also not yet clear about the sources of funding for implementing PIS-PK. On output (results of family visits), there are differences in the results of the calculation of indicators between the results of data collection conducted by PIS-PK puskesmas officers and study results. When compared between the two puskesmas, Puskesmas H Semarang is more ready for PIS-PK than Puskesmas P in Labuan Batu Regency. It can be concluded that in the implementation of PIS-PK in both puskesmas still encountered problems, both in terms of inputs (personnel, funds, tools and methods), processes (planning, implementation, supervision), and output. As a suggestion, there needs to be more comprehensive planning in implementing PIS-PK. Keywords: PIS-PK, evaluation research, input, process, and output indicator ABSTRAK Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) merupakan program upaya penguatan kesehatan dasar yang mulai dilaksanakan pada tahun 2015. Untuk mendapatkan data dan informasi yang lebih komprehensif tentang pelaksanaan PIS-PK, pada tahun 2017 Puslitbang Upaya Kesehatan Masyarakat melakukan studi evaluasi PIS-PK di beberapa kabupaten/kota di Indonesia. Studi ini menggunakan pendekatan kuantitatif dan kualitatif, di salah satu puskesmas di Kabupaten Labuan Bajo, Provinsi Sumatera Utara dan Kota Semarang, Provinsi Jawa Tengah. Pengumpulan data dilakukan dengan cara wawancara mendalam mengenai pelaksanaan PIS PK meliputi indikator input (tenaga, dana, alat dan metode), proses (perencanaan, pelaksanaan, pengawasan), dan output. Hasil studi menunjukkan bahwa pelaksanaan untuk indikator input, seperti masih terbatasnya SDM puskesmas dalam melakukan pendataan maupun entri data, juga belum jelasnya sumber pembiayaan pelaksanaan PIS-PK. Pada output (hasil kunjungan keluarga) terdapat perbedaan hasil perhitungan indikator antara hasil pendataan yang dilakukan oleh petugas PIS-PK puskesmas dengan hasil studi. Jika dibandingkan diantara ke dua puskesmas, Puskesmas H Kota Semarang lebih siap PIS-PK daripada Puskesmas P Kabupaten Labuan Batu. Dapat disimpulkan bahwa dalam pelaksanaan PIS-PK di kedua puskesmas masih menemui permasalahan, baik dalam hal input (tenaga, dana, alat dan metode), proses (perencanaan, pelaksanaan, pengawasan), maupun output. Sebagai saran, perlu adanya perencanaan yang lebih komprehensif dalam implementasi PIS-PK. Kata kunci: PIS PK, riset evaluasi, Indikator input, proses, dan output